2014
DOI: 10.1155/2014/614342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ARIMA and Artificial Neural Networks Models for Stock Price Prediction

Abstract: This paper examines the forecasting performance of ARIMA and artificial neural networks model with published stock data obtained from New York Stock Exchange. The empirical results obtained reveal the superiority of neural networks model over ARIMA model. The findings further resolve and clarify contradictory opinions reported in literature over the superiority of neural networks and ARIMA model and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
218
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(234 citation statements)
references
References 22 publications
9
218
0
7
Order By: Relevance
“…In fact, even if there are a large sample data, but it does not necessarily find rule, even if there is a statistical rule, but it is also not a typical. The other is the artificial intelligence technique such as artificial neural network (ANN) [3][4][5], genetic algorithm (GA) [6,7], and many hybrid intelligent algorithms [8][9][10][11]. The hybrid intelligent algorithms have more flexibility to solve the complex models, so more and more researchers tend to use them to deal with forecasting problems.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, even if there are a large sample data, but it does not necessarily find rule, even if there is a statistical rule, but it is also not a typical. The other is the artificial intelligence technique such as artificial neural network (ANN) [3][4][5], genetic algorithm (GA) [6,7], and many hybrid intelligent algorithms [8][9][10][11]. The hybrid intelligent algorithms have more flexibility to solve the complex models, so more and more researchers tend to use them to deal with forecasting problems.…”
Section: Introductionmentioning
confidence: 99%
“…The ARIMA(A1), plays a role of a reference model being an implementation of the simple bandwidth predictor specified in (5). For the estimation of ARIMA parameters, we used the routines implemented in the arima library, which is a part of the standard CRAN R distribution [21].…”
Section: Modelmentioning
confidence: 99%
“…measuring the time needed to download a chunk of video, or from a model of network traffic. In this case, the estimator returns the output of the models detailed in Table 3, taking into account that the output of ARIMA(A1) is just an averaged measurement of network traffic intensity in several previous periods (5).…”
Section: Models Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained revealed that the ARIMA model has a strong potential for short-term prediction. The forecasting performance of ARIMA and artificial neural networks model [5] has been examined with New York Stock Exchange data. The empirical results obtained prove the superiority of neural networks model over ARIMA model.…”
Section: Introductionmentioning
confidence: 99%